Lactic acid bacteria with a strong antioxidant function isolated from “Jiangshui,” pickles, and feces - Hu, Yue; Zhao, Yan; Jia, Xu; Liu, Dan; Huang, Xinhe; Wang, Cheng; Zhu, Yanhua; Yue, Changwu; Deng, Shanshan; Lyu, Yuhong (Frontiers in Microbiology, 2023)
Excessive free radicals and iron death lead to oxidative damage, which is one of the main causes of aging and diseases. In this field of antioxidation, developing new, safe, and efficient antioxidants is the main research focus. Lactic acid bacteria (LAB) are natural antioxidants with good antioxidant activity and can regulate gastrointestinal microecological balance and immunity. In this study, 15 LAB strains from fermented foods or feces were evaluated in terms of their antioxidant attributes. The scavenging rate of 2,2-diphenyl-1-picrylhydrazyl (DPPH), hydroxyl radicals, and ferrous ion-chelating of these strains ranged from 28.81–82.75%, 6.54–68.52%, and 9.46–17.92%, respectively, while the scavenging superoxide anion scavenging activity exceeded 10%. According to all the antioxidant-related tests, strains possessing high antioxidant activities J2-4, J2-5, J2-9, YP-1, and W-4 were screened. The five strains demonstrated tolerance to 2 mM hydrogen peroxide. The adhesion of the screened strains to the intestinal tract was examined using hydrophobic and auto-aggregation tests. The safety of the five strains was analyzed based on their minimum inhibitory concentration and hemolysis, and 16S rDNA was used for molecular biological identification. J2-4, J2-5, and J2-9 were Lactobacillus fermentans and γ-hemolytic (non-hemolytic). YP-1 and W-4 were Lactobacillus paracasei and α-hemolytic (grass-green hemolytic). Although L. paracasei has been proven as a safe probiotic without hemolytic characteristics, the hemolytic characteristics of YP-1 and W-4 should be further studied. Due to the weak antimicrobial activity of J2-4, finally, we selected J2-5, J2-9 for cell experiment, J2-5 and J2-9 showed an excellent ability that resistant to oxidative damage by increasing SOD, CAT, T-AOC activity of 293T cells. Therefore, J2-5, and J2-9 strains isolated from Longevity Village could be used as potential antioxidants for functional food, health care, and skincare.